Analysis of Instagram Social Media Management @livingintelkom in Forming Public Opinion on the Digistar Class Program - Marvella, Sadira Ayu; Abdurrahman, Muhammad Sufyan (Jurnal Ilmiah Komunikasi Makna, 2024)
Digistar Class is a free and flexible online class program organized by PT Telkom Indonesia (Persero) Tbk through the Living in Telkom community, aiming to improve digital skills (hard skills & soft skills) for students and fresh graduates. This study analyzes Instagram social media management @livingintelkom in shaping public opinion towards the Digistar Class Program. Based on the Circular Model of SOME theory and the public opinion theory of Leonard W. Doob, this study identifies that @livingintelkom accounts successfully increase participation and positive sentiment through the strategy of "Share, Optimize, Manage, and Engage." Proper social media management, including the management of comments and direct responses, as well as the use of relevant and engaging content, has proven to be effective in attracting subscribers and building positive public opinion. Active interaction and quick response to participant input are also key in maintaining a positive image of the program in the eyes of the public. The results of the study show that this strategy has succeeded in increasing the number of registrants and strengthening positive public opinion of the Digistar Class Program.